Εξαρτησιογόνες ουσίες: Η κάνναβη πυροδοτεί την εμφάνιση σχιζοφρένειας; - Γεωργίου, Νικολέττα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: The use of addictive substances causes various symptoms such as hallucinations and delusions. Similar symptoms surface in accordance to psychotic disorders. In addition, during recent years, there is an increasing number of studies that link cannabis use with the appearance of schizophrenia. Aim: The aim of this study is to investigate whether the use of cannabis triggers the appearance of psychotic symptoms and schizophrenia. Materials and Methods: The method employed for this study was the critical review of research bibliography. Consequently, the research for the bibliography was achieved using the following databases: EBSCO, Medline, Pubmed και Google Scholar με λέξεις κλειδιά cannabis, schizophrenia, psychosis, abuse. Eventually, 11 research studies were included that fulfilled the criteria and demands of this study. Results: Going through the bibliography it became clear there is existing data which support the link between cannabis use and the appearance of psychotic disorders and schizophrenia. However, these data differentiate depending on the sex and age of the cannabis user. On the other hand, some researchers support there is no link between cannabis use and the appearance of schizophrenia. Conclusions: The research evidence drawn from the bibliography remain unclear and contradictive regarding the link between cannabis use and the appearance of psychotic disorders, leading to the conclusion that further research is essential.
Keywords: Schizophrenia; Cannabis